2022
DOI: 10.15562/bmj.v11i3.3721
|View full text |Cite
|
Sign up to set email alerts
|

Soft skills elements in structured clinical skill assessment: a qualitative study

Abstract: Introduction: The intangible nature of soft skills makes it difficult for nursing academics to evaluate nursing students' attainment of these skills. Most of the time, academics focus more on assessing nursing students' knowledge and performance (hard skills) in clinical skill assessments. In focusing primarily on assessing nursing students' hard skill competencies, the nursing profession has given inadequate attention to developing their soft skill competencies. Thus, this study aimed to explore the nursing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…A study reported that graduate nurses were not prepared as holistic nurses at the end of their nursing education programme and without giving focus on adequate soft skills assessment, students are graduating unprepared to be successful in the workplace (7). Recent studies also highlighted that soft skills assessments are really important for nursing students to revive the art of nursing (8,9). After all, nursing is a caring profession, and caring remains central to nurses' values, even above their accountability for it, but they tend to dismiss caring as unimportant in favour of other tasks deemed more important.…”
Section: Editorial Open Accessmentioning
confidence: 99%
“…A study reported that graduate nurses were not prepared as holistic nurses at the end of their nursing education programme and without giving focus on adequate soft skills assessment, students are graduating unprepared to be successful in the workplace (7). Recent studies also highlighted that soft skills assessments are really important for nursing students to revive the art of nursing (8,9). After all, nursing is a caring profession, and caring remains central to nurses' values, even above their accountability for it, but they tend to dismiss caring as unimportant in favour of other tasks deemed more important.…”
Section: Editorial Open Accessmentioning
confidence: 99%
“…Therefore, an organization is required to ensure employees possess sufficient skills to bridge the expectation gap. Accordingly, soft skill assessments among healthcare personnel are currently not put as a priority by the healthcare organization [19].…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of confirming the accuracy of this observation, it should be mentioned that research in this field has been undertaken in various sectors (occupations). For example, Gonzalez et al (2013) investigated the importance of soft skills in dentistry, Laari et al (2022) and Jamaludin et al (2022) in the nursing profession, Tankovic et al ( 2023) in the tourism industry and Lyu and Liu (2021) in the US energy sector.…”
mentioning
confidence: 99%